2009
DOI: 10.1177/0963662509347814
|View full text |Cite
|
Sign up to set email alerts
|

“… a certain amount of engineering involved”: Constructing the public in participatory governance arrangements

Abstract: This paper argues that it is time for public understanding of science to develop a critical inventory of the forms, formats and methods of public participation and their respective implications and ambiguities. It highlights the need for analysing not only the limitations and deficiencies of participatory arrangements but also their constructive dimension, in particular the construction of the subject of participation. Looking into participatory governance arrangements in the issue area of genetic testing in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 42 publications
1
119
0
2
Order By: Relevance
“…Emergent collectives of participation produce publics as well (Braun & Schultz, 2010;Michael, 2009;Pallett & Chilvers, 2013) through constructing particular identities of the actors involved, such as: 'innocent citizens' or 'pure publics' that are assumed to have limited prior knowledge of the issue in question or deemed to be 'representative' of a wider public; 'interested' or 'affected' publics who have a personal attachment to the object of participation, including through exposure to risk or illness; or more 'active' or 'innovative citizens' who are constructed as bringing about various forms of distributed action. From this perspective it is evident that TM produces participants as 'frontrunners' and SNM produces 'niche actors'.…”
Section: Participation As Emergent Relational and Co-producedmentioning
confidence: 99%
“…Emergent collectives of participation produce publics as well (Braun & Schultz, 2010;Michael, 2009;Pallett & Chilvers, 2013) through constructing particular identities of the actors involved, such as: 'innocent citizens' or 'pure publics' that are assumed to have limited prior knowledge of the issue in question or deemed to be 'representative' of a wider public; 'interested' or 'affected' publics who have a personal attachment to the object of participation, including through exposure to risk or illness; or more 'active' or 'innovative citizens' who are constructed as bringing about various forms of distributed action. From this perspective it is evident that TM produces participants as 'frontrunners' and SNM produces 'niche actors'.…”
Section: Participation As Emergent Relational and Co-producedmentioning
confidence: 99%
“…In their study of public engagement in research on new genetic technologies, Braun and Schultz (2010) found that researchers appreciate some types of public and particular subject positions more strongly than others, endowing special significance mainly to citizens [pure publics] and consumers [affected publics] while depreciating contributions from advocates and partisan organized stakeholder groups. Contra to Braun and Schultz, we found that public health and health policy researchers frequently involve advocates from stakeholder and interest groups as deliberators, especially when research is most strongly connected to policy making.…”
Section: Discussionmentioning
confidence: 99%
“…To answer research question four, we draw on critical social science scholarship (Braun & Schultz, 2010;Evans & Plows, 2007;Felt & Fochler, 2010), and recent discussion in health policy literature (Barnes et al, 2007;Litva et al, 2009;Martin, 2012), to examine how subjects of participation are conceptualized as 'the public' in deliberative public health and health policy research. It has been proposed that the conception of citizens in health policy research is ontologically shallow (Lehoux et al, 2012).…”
Section: Figure 1 Types Of Deliberative Forummentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement activities thus are framed in particular ways: they reproduce the institutional culture of those designing or implementing them (e.g. Bickerstaff et al, 2010;Braun and Schultz, 2010).…”
Section: Introduction: Engagement and Scientific Citizenshipmentioning
confidence: 99%